A revised Self- and Family Management Framework. - Grey, Margaret; Schulman-Green, Dena; Knafl, Kathleen; Reynolds, Nancy R (Nursing outlook, 2015)
Research on self- and family management of chronic conditions has advanced over the past 6 years, but the use of simple frameworks has hampered the understanding of the complexities involved.